(untitled) (Journal of Atomic and Molecular Sciences, 2022)
We present ab initio scattering calculations results of low-energy electron collision with methylamine using R-matrix approach within the static-exchange (SE) and static-exchange-polarization (SEP) approximations. The elastic integral, momentum transfer and differential cross sections are reported. The calculated elastic integral cross sections are in agreement with the available experimental and theoretical data. A σ^∗ shape resonances of ^2A' symmetry located at 8.9 eV are detected within SEP model. For this dipole molecule Born-closure procedure was used to account for the higher partial waves (l > 4) to obtain the convergence of the cross section.